The Exploration of Challenges Concerning Combat against Illegal Transboundary Movement of Plastic Waste in Thailand - Suwannakart, Phatsaporn; Pitiwararom , Rachtipan; Pumjit , Nichabha (Journal of Politics and Governance, 2025)
Thailand is one of the developing countries facing a major concern on environmental crime regarding illegal transboundary movement of plastic waste. This study sheds light on the challenges that law enforcement organizations encounter in dealing with this sort of crime. The data were collected through a qualitative approach: in-depth interviews with key informants consisting of customs officers, police, officers of the Department of Special Investigation (DSI), the Department of Industrial Works, the Pollution Control Department, legal experts, and non-governmental organizations. The findings reveal that the challenges in detecting environmental crime are linked to limited intelligence and technology for identifying data in the customs’ risk management system for product scanning as well as delayed coordination among agencies, an inactivity in monitoring factories’ importation and manufacturing in both free zone and general areas trapped by bureaucratic government procedure, officials’ insufficient knowledge in implementing the Anti-Participation in Transnational Organized Crime Act B.E. 2556 (A.D.2013) for investigation and prosecution, and an unsynchronized criminal justice agencies framework particularly in establishing the environmental crime division institution from pretrial to trial. Additionally, this study provides guidance for policymakers to address law enforcement challenges and offers recommendations for combating illegal transboundary movement of plastic waste.